A study on the variation of streaming potential coefficient with physical parameters of rocks - Thanh, Luong Duy; Sprik, Rudolf (VNU Journal of Science: Mathematics - Physics, 2017)
Streaming potential is induced by the relative motion between a fluid and a solid surface and is directly related to the existence of an electric double layer between the fluid and the solid grain surface. Streaming potential depend not only on the fluid and mineral composition of rocks but also on microstructure parameters of rocks. To investigate the variation of streaming potential with rock parameters including the effects of the variation of the zeta potential due to the difference in mineral compositions between samples, we perform streaming potential measurements on six samples of Berea sandstone saturated with four different NaCl solutions. The results show that the streaming potential coefficient strongly depends on permeability of rocks for low fluid electric conductivity. However, when the fluid conductivity is larger than a certain value, the streaming potential coefficient is completely independent of permeability. This observation is then explained by a theoretical model. Additionally, the results also show that there is no clear correlation between the streaming potential coefficient and porosity, grain density, tortuosity, formation factor, bulk modulus and or shear modulus of rocks.